Empowering course design with open educational resources (OER) in learning management systems (LMS) - Fardadvand, Shahram (My University, 2025)
The integration of Open Educational Resources (OER) with Learning Management Systems (LMS) such as Moodle and Canvas is redefining course design by enabling educators to create accessible, flexible, and dynamic learning experiences. This session explores how Pressbooks, an open-source publishing platform, improves LMS capabilities by simplifying the integration of Open Educational Resources (OER) into well-structured course designs. Pressbooks offers powerful export options for designing courses that combine chapters and materials from diverse OER sources. Educators can remix, adapt, and integrate content into unified course modules while retaining the interactivity and accessibility essential for today’s learners. This presentation demonstrates how Pressbooks empowers educators to build flexible courses tailored to their curriculum by embedding resources directly within LMS platforms. Educators can improve teaching by using Pressbooks’ easy integration. This integration helps deliver content better and engages learners more. Examples of successful course designs will show how combining material from different Open Educational Resources (OER) improves teaching and learning. Participants will learn to utilize Pressbooks and the LMS to create interactive, accessible, modular courses. This method provides equitable access to quality education and enables educators to tailor learning for diverse audiences.
Presented on March 5, 2025, at Global Open Education Week 2025, held at the University of Windsor in Windsor, Ontario, Canada.
Keywords: Open Educational Resources (OER); Learning Management Systems (LMS); course design; Pressbooks